LATGALIAN VOCABULARY AND IDIOMS RELATED TO SPINNING - Ūdre, Sandra (Via Latgalica, 2016)
Spinning (rotation) as a physical phenomenon is an interesting thing. Many archaic notions remain in the language of the dominating perceptions of physical phenomena. Specific studies associated with the Latgalian language have determined that the use of various Latgalian lexemes in contemporary texts creates problems with archaic semantics. These are practical questions for users of Latgalian (primarily writers): which synonym is more appropriate – „doncuot” or „dzyguot” (both meaning ‘to dance’)? Are these terms equivalent? Does the word „maule” (meaning ‘wheel hub’) have only one meaning, even when used in the interjection „ot, maule!”? Why, in Latgalian, does snow spin („snīgs grīž”), but in standard Latvian different words and a different sentence structure must be used for the same expression? This study not only answers these particular questions of lexeme semantics in use, but will also use the linguoculturological approach to discuss the following thematic arcs in Latgalian phraseology and lexicon: 1) signs of natural processes and tools; 2) characteristics of the weather; 3) signs of the process of dancing; 4) lexemes representing the semantics of chaos. An archaic understanding of spinning in language is associated with the concept of the mystic triangle (underworld, world and heaven) model of the world, in which one of the ways to tear down the boundaries between the worlds is to spin in an uncontrollably fast spiral vortex. This notion is reminiscent of Stephen Hawking’s theory of singularity in black holes.